Towards the approach to database structure generation from business rules based on natural language expressions - Kopp, A. M.; Orlovskyi, D. L. (Одеська національна академія харчових технологій, 2020)
This paper presents the approach to the database structure design using the translation from business rules based on natural language expression written in English language into SQL scripts. Business rules are translated into database tables, columns, and relations based on foreign keys. A software prototype of business rules translation into SQL statements is described, as well as its usage example is considered.
Keywords: rapid application developmen; business-rules; database management system; structured query language